Cucumber (Cucumis sativus L.) Growth and Productivity Optimization through the Application of Various Types of Organic Fertilizers - Puspita, Diah Eka (Universitas Serambi Mekkah, 2025)
Abstract The effect of soil processing and type of organic fertilizer on the growth and yield of cucumber plants (Cucumis Sativus L.). The research was carried out on the Gampong Baroh Lancok Land, Jln. Cot Mondaroi, Bandar Baru District, Pidie Jaya Regency, in April - June 2024. This research used non factorial Randomized Block Design (RAK). There is one factor studied, namely the influence Provision of Organic Fertilizer (O) consists of 4 levels, namely: O1 = Control, O2 = Organic Granule Fertilizer, O3 = Cow manure and O4 = Compost fertilizer. Observations in this study included number of fruit, fruit length and fruit weight. The results of the research, the treatment of providing organic fertilizer had a very significant effect on fruit length, fruit and fruit weight, but had no significant effect on the number of fruit on cucumber plants. The best treatment is found in organic cow manure fertilizer (O2).